Motivasi eksternal dan internal perawat dengan penerapan pasien safety - Esti Handayani; Eka Yudha Chrisanto; M. Arifki Zainaro (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: Based on data at the inpatient, it was reported that the Near Miss (NM) of the Tegineneng inpatient health center was 10.5%, the Near Miss (NM) 6.15%, and in Kedondong reported an indicator of complete initial clinical assessment of 50%, Wash Your Hands With Soap compliance of 80%, and the use of PPE of 80%. Inpatient Hanura reported the incidence of nosocomial infections in 2018 was 7, and in 2018 was 7.30%, and in 2019 it increased to 7.60%.Purpose: To know the relationship between external and internal motivation of nurses with the application of patient safety in inpatient health centers.Method: Quantitative research design, descriptive correlative research design using cross sectional study, population and sample in this study were 40 respondents, data analysis used univariate and bivariate using chi square test.Results: The distribution of respondents knowledge about the external motivation of nurses with good application of patient safety was 20 respondents 55.0%, 18 respondents 45.0 % poorly, then the internal motivation of nurses with the application of good patient safety was 32 respondents 80.0%, less good as many as 8 respondents 20.0% the results of statistical tests using the chi square test obtained p-value = 0.289 (> 0.05), p-value = 0.049 ( > 0.05).Conclusion: p-value = 0.385 (> 0.05), which means that there is no relationship between the external motivation of nurses and the application of patient safety. The results of statistical test using the chi square test obtained P-value = 0.049 (> 0.05), which means that there is a relationship between the internal motivation of nurses and the application of patient safety.Keyword: Motivation; Internal; External; Patient; Safety.Pendahuluan: Berdasarkan data di UPT Puskesmas Rawat Inap dilaporkan angka kejadian tidak diharapkan (KTD) Puskesmas Rawat Inap Tegineneng sebesar 10.5 %, Kejadian Nyaris Cidera (KNC) 6.15%. Puskesmas Rawat Inap Kedondong dilaporkan Indikator Pengkajian Awal Klinis yang terisi lengkap sebesar 50%, Kepatuhan Cuci Tangan Dengan Sabun 80%, dan penggunaan APD 80%. Puskesmas Rawat Inap Hanura dilaporkan Kejadian Infeksi Nosokomial tahun 2018 sebesar 7.30% dan di tahun 2019 meningkat menjadi 7.60%.Tujuan: Diketahui hubungan motivasi eksternal dan internal perawat dengan penerapan pasien safety di puskesmas rawat inap.Metode: Penelitian kuantitatif, rancangan penelitian deskriptif korelatif dengan menggunakan rancangan cross sectional study, populasi dan sampel dalam penelitian ini adalah perawat sebanyak 40 responden, analisa data menggunakan univariat dan bivariat menggunakan uji chi square.Hasil: Distribusi pengetahuan responden tentang motivasi eksternal perawat dengan penerapan pasien safety baik sebanyak 20 responden (55.0%), buruk sebanyak 18 responden (45.0%), kemudian motivasi internal perawat dengan penerapan pasien safety baik sebanyak 32 responden (80.0%), buruk sebanyak 8 responden (20.0%). Hasil uji statistik menggunakan uji chi square didapat nilai p-value=0.289 (>0,05), p-value =0.049 (>0.05).Simpulan : p-value =0.289 (>0.05) yang artinya tidak terdapat hubungan motivasi eksternal perawat dengan penerapan pasien safety. Hasil uji statistik menggunakan uji chi square didapat nilai p-value=0,049 (>0.05) yang artinya ada hubungan motivasi internal perawat dengan penerapan pasien safety.